2021
DOI: 10.1186/s12883-021-02186-9
|View full text |Cite
|
Sign up to set email alerts
|

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial

Abstract: Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Learning to play golf mainly consists of performing different swings (full swing, pitch, chip, put) and golf-specific rules. In a recently published 22-week randomized trial, a significant effect of learning to play golf on attention performance was found in elderly people with SMC 36 . The findings may suggest that learning to play golf has an impact on specific cognitive domains, such as attention.…”
Section: Introductionmentioning
confidence: 99%
“…Learning to play golf mainly consists of performing different swings (full swing, pitch, chip, put) and golf-specific rules. In a recently published 22-week randomized trial, a significant effect of learning to play golf on attention performance was found in elderly people with SMC 36 . The findings may suggest that learning to play golf has an impact on specific cognitive domains, such as attention.…”
Section: Introductionmentioning
confidence: 99%
“…It is, however, to be noted that the cross-sectional study only made this comparison as a single time point, and thus cannot determine causality [49]. In addition, aerobic performance determined through VO 2 max [45] or 6-min walking test did not differ between golfers and controls [50], while submaximal exercise performance improved after golf training with lower SBP, HR at 100 W [45], and lower oxygen consumption, HR and lactate at 7 METs [36].…”
Section: Cardiovascular Effectsmentioning
confidence: 89%
“…Shimada et al ( 2018 ) found improvements in immediate and delayed logical memory after a 24‐week golf training with healthy older adults. Learning to play golf over 22 weeks improved cognitive functions and the regulation of dysregulation of the kynurenine pathway that affects cognition in elderly people (Stroehlein et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%